Fig. 3 in Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland ... - Skovsted, Christian B.; Peel, John S. (Zenodo, 2007)
Fig. 3. Trilobites, echinoderms, and sponges from the Lower Cambrian, Forteau Formation (Western Newfoundland). A. Dorypygidae indet., internal mould of fragmentary cephalon, NFM−671 from ICS 1421; in dorsal (A1) and left lateral (A2) views. B. Calodiscus lobatus (Hall, 1847), NFM−672, dorsal view of silicified cephalon. C. Ptychoparioid indet., NFM−673 from ICS 1421, silicified cephalon. D. Olenellid indet., NFM−674 from ICS 1421, dorsal view of silicified juvenile cephalon. E–J. Phosphatised echinoderm ossicles. E. Morphotype 1, NFM−675, dorsal view. F. Morphotype 1, NFM−676, dorsal view. G. Morphotype 1, NFM−677, ventral view. H. Morphotype 2, NFM−678, ventral view. I. Morphotype 2, NFM−679, dorsal view. J. Morphotype 2, NFM−680, oblique lateral view. K. Hexactinellid spicule, NFM−681, scale bar 100 ̊m. All specimens from JSP 1982−01 unless otherwise stated. All scale bars except K 500 ̊m. ... : Published as part of Skovsted, Christian B. & Peel, John S., 2007, Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland, pp. 729-748 in Acta Palaeontologica Polonica 52 (4) on page 733, DOI: 10.5281/zenodo.13741171 ...